DEVELOPING FAMILY VALUES IN ADOLESCENTS DEPRIVED OF PA-RENTAL CARE - Molozhavenko, Vera; Butina, Yulia (Revista Inclusiones, 2020)
Family values are important to the family and society well-being. The purpose of the research was to find out forms for developing family values in adolescents brought up in educational institutions of social service. The diagnostic tools for the research are based on assessing family values components such as cognitive, emotional, motivational and activity-based ones. The research was conducted with the target group of adolescents deprived of parental care. The authors created special social and educational conditions effective for developing each component of family values. The results of the research showed an increase in the level of all family values components